An Analysis of the Strength and Durability of Eggshell Powder-Modified Concrete Structures - Abdul Majeed; Muhammad Umair; Yaseen Jamal; Ghassan Sattar Khan; Abdul Aleem; Ans Mehmood (Spectrum of Engineering Sciences, 2024)
Because concrete is widely used, the need for cement is constantly growing. However, this causes CO2 to be emitted or included in the structural concrete. By adding or partially substituting cement with other materials while maintaining the required qualities of concrete, researchers are attempting to lower the carbon footprints of concrete. One such product is eggshell powder, a home waste product from the chicken industry that may partially substitute cement in concrete. It increases durability and strength. The goal of this study is to determine how eggshell powder affects the strength of concrete. A 1:2:4 mix ratios and a 0.5 w/c ratio were used to cast the concrete. Eighty-four standard-sized specimens were cast and tested for one, three, seven, and twenty-eight days. Densities, compressive strength, and workability (slump value) were examined. The differences between concrete with and without ESP were compared. The findings showed that, compared to a typical concrete mix, the workability of concrete reduces when eggshell powder is added. While there is a noticeable decrease in unit weight (density), adding eggshell powder content to ESP concrete sufficiently raises its compressive strength to a certain point. Keywords: Eggshell Powder, Workability, Slump Test, Density, Compressive Strength